Outcome of the public consultation on the draft guidance on the assessment of the safety of feed additives for the environment. Issue 4 (5th April 2019) - ,
Abstract : The European Food Safety Authority (EFSA) carried out a public consultation to receive input from the scientific community and all interested parties on the draft guidance on the assessment of the safety of feed additives for the environment prepared by the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) and endorsed by the Panel for public consultation at its Plenary meeting on 2 October 2018. The written public consultation for this document was open from 8 October to 19 November 2018. EFSA received a total of 133 comments from 11 interested parties. EFSA and its FEEDAP Panel wish to thank all stakeholders for their contributions. The current report summarises the outcome of the public consultation, and includes the comments received and how the comments were addressed. The FEEDAP Panel prepared an updated version of the guidance on the assessment of the safety of feed additives for the environment taking into account the questions/comments received. This guidance was discussed and adopted at the FEEDAP Plenary meeting on 27 February 2019, and is published in the EFSA Journal. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5648/full